Bone filler and adhesive at the same time: in-vitro analysis in a porcine fracture model - Stefanie Hoelscher-Doht; Nicola Zufall; Maximilian Heilig; Philipp Heilig; Martin Cornelius Jordan; Rainer Heribert Meffert; Uwe Gbureck; Lea Hüls (BMC Musculoskeletal Disorders)
Abstract Background Bone defects in the context of fracture treatment or tumor surgery represent a major challenge regarding their treatment. Sticky and drillable magnesium phosphate cements could revolutionize the intraoperative reconstruction of complex fractures close to the joint due to their properties as bone adhesive and filler at the same time, enabling the technique of first reduction of the fracture fragments by bonding with the cement and then applying stabilization with screws and/or plates. Methods Lateral split-depression fractures of the proximal tibia were generated in 27 porcine specimens, which were then randomized into 3 groups of 9 each. In group A, a new operative technique was applied by reducing the fracture using a newly formulated magnesium phosphate cement (MgP cement) and then applying stabilization by plate osteosynthesis. In the other two groups, plate osteosynthesis was performed first, as in the current standard operative procedure, followed by the injection of a bone graft substitute through a gap in the fracture area of the tibia, group B with MgP cement, group C with hydroxyapatite cement. The following parameters were determined during the cyclic testing phase of 3000 test cycles: The total displacement and the optical displacement of the lateral plateau [mm]. During load-to-failure tests, the stiffness [N/mm], the maximum load [N] and the normalized maximum load [%] were determined. Results The results revealed a comparable stability for all groups with no significant differences in all forms of displacement, with group A demonstrating the lowest values for displacement. Maximum load was highest for group C (group B; C [p = 0.04]; group A; C [p < 0.01]), however considering normalized maximum load, no significant difference between the three groups could be found. Conclusions This study presents a breakthrough approach using a bone cement as both a bone adhesive and a filler at the same time. The adhesive and drillable magnesium phosphate cement proved to be a versatile solution featuring a new surgical method in which the fracture was anatomically reduced using only the cement. Furthermore, with this new technique, the cement demonstrated comparable, if not slightly superior, biomechanical stability in the porcine tibial split depression fracture model compared to the current standard of surgical treatment using primary plate osteosynthesis and a commercial hydroxyapatite cement.